Penurunan Fungsi Sistem Penghidu Pada Pasien Penyakit Parkinson: Epidemiologi dan Tatalaksananya - Agung Riatmojo, Andi (Jurnal Syntax Fusion, 2022)
Parkinson's disease in general is a disorder of the central nervous system which most of its manifestations are motor function disorders. However, today's non-motor symptoms are found as early manifestations of Parkinson's disease. To determine the relationship between Parkinson's disease and non-motor symptoms, namely loss of smell or anosmia. The writing of this article includes various sources originating from scientific journals on online portals of journal publications such as MedScape, Google Scholar, PubMed, and NCBI, with the keywords "olfactory disorders and Parkinson's disease". Loss of smell can be the first symptom of pathological abnormalities in the central nervous system (CNS). Several studies related to Parkinson's disease stated that almost all patients studied had atrophy of the olfactory bulb, causing the patient to experience loss of smell function (anosmia). The effect of decreasing the volume of the olfactory bulb and the effect of neurotransmitters are also believed to affect the olfactory dysfunction in patients with Parkinson's disease. Anosmia is the most common non-motor symptom in Parkinson's disease, and often precedes motor symptoms in Parkinson's disease. Olfactory training is a promising modality for the treatment of olfactory dysfunction and anosmia. The results of this systematic review and meta-analysis suggest that it may be an effective treatment for olfactory dysfunction due to various etiologies